Optimization of Marine Sponge Isolated Bacterium Bacillus subtilis (MTCC No. 10619) for the Production of Antimicrobial Metabolites - RADHA KRISHNA, E.; SHAMSHER KUMAR, P.; SUJATHA , P. (Asian Journal of Chemistry, 2012)
The culture conditions were optimizing for the production of antimicrobial metabolites by Bacillus subtilis. The metabolite production was started after 24 h of incubation and reached its maximum levels after 72 h and decreased gradually. The pH was adjusted to 7.0 and temperature to 35 ºC supported the production of antimicrobial metabolites. The best proved carbon and nitrogen sources were sucrose and peptone, respectively as basal medium